Darier disease with oral and esophageal involvement: A case report - Magesh Karuppur Thiagarajan; Malathi Narasimhan; Anandan Sankarasubramanian (Wolters Kluwer Medknow Publications, 2011)
A 58-year-old man presented with itchy papular eruptions all over the body since 15 years. Intraoral examination revealed raised papular lesions on the labial mucosa, hard palate, and tongue. The histopathology of the oral and skin lesions was confirmative of Darier disease (DD). This patient also showed esophageal involvement, which was confirmed histopathologically. Such a presentation of DD, with oral and esophageal involvement, is rare.